Diagnostic evaluation and treatment of osteoarticular lesions in patients having sickle cell anemia: Literature review (Research, Society and Development, 2024)
Sickle cell anemia is a genetic disorder in which the structure of hemoglobin undergoes a significant alteration through a point mutation in the β-globin gene. When the gene is altered in sickle cell disease, hemoglobin S is expressed, causing the red blood cell to acquire the characteristic sickle shape. Thus, in the presence of this mutation, especially with changes in oxygen concentration and pH, hemoglobin S tends to polymerize, resulting in sickling of the red blood cells, leading to a shortened lifespan of red blood cells, vascular occlusion phenomena, and episodes of pain and organ damage. Among the complications caused by sickle cell disease, stroke, recurrent infections, osteoarticular disease, among others, can be mentioned. One of the complications that generates the greatest morbidity is osteoarticular lesions, which can present with symptoms such as pain, swelling, warmth, fever, reduced vascularization, and even necrosis. Therefore, this study aimed to evaluate the diagnostic methods used in osteoarticular lesions in patients with sickle cell anemia. Among the most commonly used diagnostic methods in patients with sickle cell disease suspected of osteoarticular lesions, we can emphasize imaging diagnostic methods such as X-rays, magnetic resonance imaging (MRI), scintigraphy, and PET-CT, which can be used to differentiate between different types of lesions and suspected infectious processes, such as osteomyelitis. Therefore, imaging diagnostic methods are essential in identifying the lesion and the best treatment, with total hip arthroplasty being the most invasive method, although it is often the initial choice due to the severity of the lesion, or it is used after unpromising results from other less invasive procedures, such as femoral head decompression, grafting, and subchondroplasty.